2002
DOI: 10.1021/ja020063c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Rhodium(III)-Catalyzed Hydrogenation of Carbon Dioxide into Formic Acid. Significant Differences in Reactivity among Rhodium(III), Rhodium(I), and Ruthenium(II) Complexes

Abstract: The title reaction was theoretically investigated, where cis-[RhH(2)(PH(3))(3)](+) and cis-[RhH(2)(PH(3))(2)(H(2)O)](+) were adopted as models of the catalyst. The first step of the catalytic cycle is the CO(2) insertion into the Rh(III)-H bond, of which the activation barrier (E(a)) is 47.2 and 28.4 kcal/mol in cis-[RhH(2)(PH(3))(3)](+) and cis-[RhH(2)(PH(3))(2)(H(2)O)](+), respectively, where DFT(B3LYP)-calculated E(a) values (kcal/mol unit) are given hereafter. These results indicate that an active species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 51 publications
3
75
1
1
Order By: Relevance
“…The concerted insertion mechanism is different from the previously reported concerted mechanisms in that there is no initial interaction of an O atom with or coordination of an O atom to the metal center. [20][21][22]30] This relatively small activation energy is in good agreement with the facile CO 2 insertion observed experimentally. Ab initio metadynamics studies also confirmed very facile insertion of CO 2 into RuH 2 complexes with the same concerted insertion mecha- …”
supporting
confidence: 89%
“…The concerted insertion mechanism is different from the previously reported concerted mechanisms in that there is no initial interaction of an O atom with or coordination of an O atom to the metal center. [20][21][22]30] This relatively small activation energy is in good agreement with the facile CO 2 insertion observed experimentally. Ab initio metadynamics studies also confirmed very facile insertion of CO 2 into RuH 2 complexes with the same concerted insertion mecha- …”
supporting
confidence: 89%
“…[22,23] To systematically vary the electronic structure of the rhodium complexes and explore steric influences on the reactivity of the CO 2 association and insertion, we turned to rhodium pincer complexes, which consist of one metal center surrounded by a tridentate ligand in a meridional fashion. Depending on the three donor atoms X, Y, Z, the ligands are usually denominated as XYZ pincers.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative coupling is promoted further by the coordinative unsaturation of cationic rhodium complexes. As supported by theoretical studies [57], Brønsted acid co-catalysts likely circumvent highly energetic four-centered transition structures A for s-bond metathesis, as required for direct hydrogenolysis of metallacyclic intermediates, as follows. Metallacycle protonolysis, which may itself occur through the six-centered transition structure B, delivers a rhodium carboxylate, which then engages in hydrogenolysis through the six-centered transition structure C (Scheme 8.6).…”
Section: Hydrogenative Vinylation Of Carbonyl Compounds and Iminesmentioning
confidence: 97%